1995
DOI: 10.21273/jashs.120.6.971
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Nutrition and Soil Nutrients Are Affected by Irrigation Frequency and Method for NP-Fertigated `Gala' Apple

Abstract: `Gala' apple (Malus domestica Borkh) on M.26 rootstock was subjected, in the first five growing seasons, to NP-fertigation and a factorial combination of treatments involving method and frequency of irrigation. Two types of emitters (drip or microjet) were used to apply the same quantity of water at high (daily), intermediate (about weekly) and low (about bi-weekly) irrigation frequencies. Although initial tree vigor and yield were higher for drip-fertigated trees, by the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…The reduced colour of fruit from trees with the FD irrigation system may have been due to a higher canopy temperature (data not shown), higher total N per leaf, N cm -2 leaf (Table II), and/or leaf Mg concentration (Table V), that might have resulted in more chlorophyll production, leading to less fruit colour. Neilsen et al (1995) reported that 'Gala' apple trees that received micro-sprinkler irrigation had higher leaf P, K, and Cu, but lower leaf N, Mg, and Mn concentrations than those that received drip irrigation, which is in general agreement with our results.…”
Section: Effects Of Irrigation On Tree Size Leaf Weight Leaf Area supporting
confidence: 92%
See 1 more Smart Citation
“…The reduced colour of fruit from trees with the FD irrigation system may have been due to a higher canopy temperature (data not shown), higher total N per leaf, N cm -2 leaf (Table II), and/or leaf Mg concentration (Table V), that might have resulted in more chlorophyll production, leading to less fruit colour. Neilsen et al (1995) reported that 'Gala' apple trees that received micro-sprinkler irrigation had higher leaf P, K, and Cu, but lower leaf N, Mg, and Mn concentrations than those that received drip irrigation, which is in general agreement with our results.…”
Section: Effects Of Irrigation On Tree Size Leaf Weight Leaf Area supporting
confidence: 92%
“…The rootstock can also influence scion leaf and fruit mineral concentrations and, thus, indirectly affect fruit quality and yield (Fallahi et al, 2001b, c). Neilsen et al (1995) reported that 'Gala' apple trees irrigated using a micro-jet irrigation system had higher leaf P, K, and Cu, but lower leaf N, Mg, and Mn concentrations than trees irrigated with a drip system.…”
mentioning
confidence: 99%
“…The plots in this experiment were split, with two replicates of each treatment planted to 'Royal Gala' and two to 'Regal Gala'. A more detailed description of these experiments was published previously (Neilsen et al, 1995(Neilsen et al, , 1999.…”
Section: Description Of the Vascular Nodulesmentioning
confidence: 99%
“…Increased irrigation frequency with the same total amount of water has been used to reduce nutrient leaching and compensate for possible nutrient deficiency, and it has varying effects on plant growth and nutrient uptake (Fare et al, 1994;Scagel et al, 2011). Neilsen et al (1995) reported that higher frequency irrigation improved tree growth of 'Gala' apple (Malus domestica Borkh.) compared with lower irrigation frequency.…”
mentioning
confidence: 99%